(untitled) (Indian Journal of Public Health Research & Development, 2020)
Occupational stress or stress related to workplace refers to stress experienced as a direct result of an individual’s occupation. or job. Stress completely disturbs the physical, psychological and financial balances of an employee as well as employers. Due to stress employers cannot expect anticipated outcome from employees who are burnt out, drained or stressed, resulting in loss of their drive, determination, clarity and innovative thinking. Resilience is not just one’s capability to recover from stress, but also ability to adjust in the face of difficult situations. There is an inverse relationship exists between stress and resilience.